Combining electrochemical and imaging analyses to understand the effect of electrode microstructure and electrolyte properties on redox flow batteries. (15th January 2022) - Simon, Benedict A.; Gayon-Lombardo, Andrea; Pino-Muñoz, Catalina A.; Wood, Charles E.; Tenny, Kevin M.; Greco, Katharine V.; Cooper, Samuel J.; Forner-Cuenca, Antoni; Brushett, Fikile R.; Kucernak, Anthony R.; Brandon, Nigel P.
Graphical abstract: Highlights: Electrode permeability correlates best with electrode performance. Distinct inter- and intra- pore transport processes effect on performance metrics. Combined complementary experimental/modelled analysis of flow through electrodes. Carbon cloth electrodes display best permeabilities and mass transport coefficients. Custom Weka three-dimensional segmentation technique for improved image analysis. Abstract: Reducing the cost of redox flow batteries (RFBs) is critical to achieving broad commercial deployment of large-scale energy storage systems. This can be addressed in a variety of ways, such as reducing component costs or improving electrode design. The aim of this work is to better understand the relationship between electrode microstructure and performance. Four different commercially available carbon electrodes were examined – two cloths and two papers (from AvCarb® and Freudenberg Performance Materials) – and a comprehensive study of the different pore-scale and mass-transport processes is presented to elucidate their effect on the overall cell performance. Electrochemical measurements were carried out in a non-aqueous organic flow-through RFB with these different electrodes, using two supporting solvents (propylene carbonate and acetonitrile) and at a variety of flow rates. Electrode samples were scanned using X-ray computed tomography, and a customised segmentation technique was employed to extract several microstructural parameters. A pore network model was used to calculate the pressure drops and permeabilities, which were found to be within 1.26 × 10 −11 and 1.65 × 10 −11 m 2 for the papers and between 8.61 × 10 −11 and 10.6 × 10 −11 m 2 for the cloths. A one-dimensional model was developed and fit to polarisation measurements to obtain mass-transfer coefficients, k m, which were found to be between 1.01 × 10 −6 and 5.97 × 10 −4 m s −1 with a subsequent discussion on Reynolds and Sherwood number correlations. This work suggests that, for these fibrous materials, permeability correlates best with electrochemical cell performance. Consequently, the carbon cloths with the highest permeability and highest mass-transfer coefficients, displayed better performances.